Reuse of Iraqi Agricultural Drainage Water Using Nanofiltration - Abid, Mohammad F.; Al-Naseri, Saadi K.; Abdullah, Samirra N. (Journal of Membrane and Separation Technology, 2013)
Irrigated areas between Euphrates and Tigris rivers in Iraq suffer from salinity buildup in the root zone of corps. Agricultural drain water (ADW) from these areas is collected in a single main drain canal, in an annual flow rate of about 6 billion cubic meter. In the present work, a pilot-scale nanofiltration membranes unit was used to evaluate the feasibility of desalinating ADW from the main drain canal for further reuse. Bench scale experiments were conducted to determine the optimum anti-scale dosage values in the unit. These values were verified in a plate type laboratory scale NF membrane to visually monitor the onset of crystal appearance behavior. A method for calcium sulfate precipitation control is presented and an empirical correlation of anti-scale dosage as a function of concentration factor (CF) was obtained. A pilot-scale unit was used to investigate the performance of NF membrane. High rejection values for both cations and anions indicate that the use of NF membrane in desalinating ADW from the Iraqi main drain canal is promising. The treated drainage water is considered good for irrigation when classified according to Wilcox classification.